UPAYA PENINGKATAN HASIL BELAJAR KETERAMPILAN LEMPAR DAN TANGKAP MENGGUNAKAN MODEL PEMBELAJARAN COOPERATIVE LEARNING - Illham Pratama Deddy Widjaja; Taufiq Hidayat; Yolespana Qoriawan (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
The purpose of this study was to know if the learning outcomes of the materials basic manipulative motion material are better with the application of cooperative learning models in learning the ability to throw and catch class IV. IV grade school students of SD Negeri Kapasan V/147 Surabaya , were the sample of this study, totaling 29 students. Classroom action research using a spiral cycle was utilized for this research Results obtained in the first cycle showed that the completeness or achievement of manipulative basic movement skills in throwing and catching motion material showed an average score of 67. In cycle II, the completeness of the value of manipulative basic movement skills in throwing and catching material was 75 and in cycle III an increase in completeness was obtained by 14 points to 89. In each cycle, the learning outcomes of basic manipulative movement material increased when given treatment in the model cooperative learning.